The Retirement Expectations of Middle‐aged Australians - Cobb-Clark, Deborah; Stillman, Steven (My University, 2009)
We use HILDA data to examine the retirement plans of middle-aged Australians. We find that approximately two-thirds of men and more than half of women report a numeric expected retirement age which we refer to as having a standard retirement plan. Still, one in five individuals seem to have delayed their retirement planning and approximately 1 in 11 either does not know when he or she expects to retire or expects to never retire. Retirement plans are closely related to current labour market position, with workers in jobs with well-defined superannuation benefits more likely to report numeric expected retirement ages.
Economic Record
Keywords: Ageing -- Retirement; Ageing; Ageing; Retirement; Ageing